Beginning iPhone and iPad web apps : scripting with HTML5, CSS3 and JavaScript - Apers, Chris (Apress, 2010)
Provides information on Mobile Web Standards, the features of the iPhone and iPad, and how to develop successful applications using WebKit, Mobile Safari, HTML5, and CSS3.